1975
DOI: 10.1113/jphysiol.1975.sp010925
|View full text |Cite
|
Sign up to set email alerts
|

On the association between transmitter secretion and the release of adenine nucleotides from mammalian motor nerve terminals.

Abstract: SUMMARY1. Conventional electrophysiological techniques were used to record from isolated rat phrenic nerve-hemidiaphragm preparations. After periods of rest (20 min) or nerve stimulation (7/sec for 20 min) the bathing medium of the preparation was removed and assayed for adenosine triphosphate (ATP) and adenosine diphosphate (ADP) using a sensitive modification of the firefly luciferase method (Silinsky, 1974 6. These results in conjunction with experiments on the hydrolysis of exogenous ATP suggest that ATP i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
157
0
1

Year Published

1987
1987
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 329 publications
(163 citation statements)
references
References 27 publications
(46 reference statements)
5
157
0
1
Order By: Relevance
“…Recently, osteoclasts derived from mouse bone marrow were shown to express all P2 receptors, with the exception of the P2X6 and P2Y 4 receptors [119]. This study also demonstrated large differences in the expression levels of the different P2 receptors, with the P2Y 6 receptor being the most abundant [119].…”
Section: P2 Receptor Expression By Osteoclastssupporting
confidence: 54%
See 4 more Smart Citations
“…Recently, osteoclasts derived from mouse bone marrow were shown to express all P2 receptors, with the exception of the P2X6 and P2Y 4 receptors [119]. This study also demonstrated large differences in the expression levels of the different P2 receptors, with the P2Y 6 receptor being the most abundant [119].…”
Section: P2 Receptor Expression By Osteoclastssupporting
confidence: 54%
“…Recently, activation of the P2Y 6 receptor by UDP has been shown to stimulate osteoclast formation and activity [119]. Consistent with a role for this receptor in bone resorption, osteoclasts derived from P2Y 6 receptor knockout mice displayed defective function [119]. Analysis of P2Y 6 receptor knockout mice by μCT revealed increased cortical bone in the long bones and spine [119].…”
Section: Functional Effects Of P2 Receptor-mediated Signalling In Ostmentioning
confidence: 85%
See 3 more Smart Citations